Arachidonic acid-stimulated platelet tests: Identification of patients less sensitive to aspirin treatment. (17th November 2015) - Temperilli, Flavia; Rina, Aldona; Massimi, Isabella; Montemari, Anna Lisa; Guarino, Maria Luisa; Zicari, Alessandra; Pulcinelli, Fabio M.
Abstract: Serum thromboxane-B2 (TxB2), together with arachidonic acid (AA)-induced platelet aggregation, are, at the moment, the most used tests to identify patients displaying high on-aspirin treatment platelet reactivity (HAPR). Both tests are specific for aspirin action on cyclooxygenase-1. While the correlation between serum TxB2 assay and clinical outcome is established, data are conflicting with regard to aspirin treatment and a possible association with AA-stimulated platelet markers and clinical outcome. To understand such discrepancy, we performed a retrospective study to compare both assays. We collected data from 132 patients receiving a daily dose of aspirin (100 mg/day) and data from 48 patients receiving aspirin on alternate days. All Patients who received a daily dose of aspirin were studied for AA-induced platelet aggregation together with serum TxB2 levels and AA-induced TxB2 formation was also studied in 71 patients out of entire population. Consistent with recommendations in the literature, we defined HAPR by setting a cut-off point at 3.1 ng/ml for serum levels of thromboxane B2 and 20% for AA-induced platelet aggregation. According to this cut-off point, we divided our overall population into two groups: (1) TxB2 < 3.1 ng/ml and (2) TxB2 > 3.1 ng/ml. We found low agreement between such tests to identify patients displaying HAPR. Our results show that AA-induced platelet aggregation >20% identify a smaller number of HAPR patients in comparison with TxB2. A good correlation between serum TxB2 and arachidonic acid-induced TxB2 production was found ( r  = 0.76619).